Implementasi Kebijakan Perhutanan Sosial Skema Hutan Kemasyarakatan (Studi Kasus Peraturan Adat (Ri’i) sebagai Penunjang Kebijakan Perhutanan Sosial di Hutan Kemasyarakatan Wolobobo, Desa Turekisa, Kecamatan Golewa Barat, Kabupaten Ngada, Flores, Nusa - Maria Manggiasih Meo Due; Maria M. E. Purnama; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Problems that in forest areas are usually damage done by people who live around forest areas. The damage that usually occurs is forest fires, illegal logging, and encroachment. Within the Wolobobo HKm area, damage such as encroachment was still found until 2001 with a total land area of ​​481 hectares. To avoid a higher level of damage, the government, namely UPT KPH Ngada Regency together with the LSM Serbio Ngada, took a middle path by making the Ri'i customary regulation which was proclaimed on November 8, 2003. Over time, the government established the Wolobobo HKm area with a forest function as HP (Production Forest) in 2010 and the establishment of Social Forestry in 2016.The research was carried out in the HKm Wolobobo area, Bajawa, Ngada Regency, this research was conducted to find out the Implementation of Social Forestry Policy and the Implementation of Ri'i Customary Regulations. The research was conducted for 2 months June - August 2022. Respondents in this study came from five KTH with a total of 72 members. The method used in this study is qualitative. The results of the research obtained through the interview method with the help of a questionnaire found that the Implementation of Social Forestry Policy and the Implementation of Ri'i Customary Regulations had not gone well because the UPT KPH in Ngada Regency was not optimal in conducting outreach and assistance to the management community and the low level of good human resources from both quantity and quality.